PELAKSANAAN SOSIALISASI KOMISI PENYIARAN INDONESIA DAERAH SUMATERA BARAT (KPID SUMBAR) DALAM MENJALANKAN TUGAS DAN WEWENANG BERDASARKAN UNDANG-UNDANG NOMOR : 32 TENTANG PENYIARAN - Yumi Ariyati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The Indonesian Broadcasting Commission (KPI) as an independent state institution has the duties and authority as regulated by Law Number 32 of 2002 concerning Broadcasting. Among other tasks and functions are to compile regulations and set guidelines for broadcasting behavior and set broadcast program standards.In fact limited budget received every year, the West Sumatra KPID has carried out socialization activities through Public Service Announcements, Talk shows, Public Dialogue, Media Literacy, Brochures and Distribution of Public Complaints Boxes in several Regencies / Cities in the hope that this will help the existence of the West Sumatra KPID his duties and authorities are based on law number 32 regarding Broadcasting.